Investigation of the dependencies of the Vivaldi antenna with a resonator in the electrodynamic modeling software complex - T. G. Aslanov; S. A. Ibragimov (Вестник Дагестанского государственного технического университета: Технические науки, 2024)
Objective. The goal of the study is to optimize a computer model of a Vivaldi antenna with conductive plates on the same side as the resonator.Method. The study is based on electrodynamic modeling methods.Result.The paper presents a computer model of a Vivaldi antenna with conductive plates on one side with a resonator. A comparative analysis of two types of Vivaldi antennas was carried out of the dependence of the beam width and the voltage standing wave ratio on the radius of the current-conducting plate curve in the form of lobes and the values of the opening in two planes θ = 900 (the plane of the antenna's opening) and φ = 00 (the plane perpendicular to the antenna's opening plane) in the frequency range from 3 to 24 GHz. The influence of the shape, size and position of the resonator on the SWR value and the width of the antenna radiation pattern was determined. VSWR values are given for different shapes and sizes of the resonator. The main parameters of the resonator have been identified, which affect the characteristics of the antenna.Conclusion. Electrodynamic modeling allows us to obtain a Vivaldi antenna with the required radiation pattern width with an improved standing wave ratio.